COMPARATIVE ANALYSIS OF THE PRESENTATION OF FINANCIAL STATEMENTS ON CONVENTIONAL BANK AND SYARIAH BANK - Tatas Ridho Nugroho; Ahmad Ahmad (Universitas Gajayana Malang, 2018)
Abstract : The principle difference in banking, commonly referred to as conventional banking with syariah banking. The difference in principle leads to differences in its policy system, especially on the systems and policies in reporting the financial statements applied. The purpose of this study is to compare the financial statements of conventional banking and syariah. This research method is qualitative approach with comparative descriptive analysis. The sample in this research is Bank BCA representing Conventional Bank and Bank Muamalat representing Syariah Bank. The activities of these two banks are generally not different, but if there are other activities of these two banks, there are differences, such as ZIS or Zakat. Conventional banking with Syariah banking when viewed in general, the financial statements are different from each other, where in conventional banking there are 5 types of financial statements, while in Islamic banking there are 8 types of financial statements. Keywords: conventional bank, syariah bank, financial statement, banking